Upper pleistocene and holocene palaeoenvironments in the Southern Cape : the micromammalian evidence from archaeological sites - Avery, D. M.(Diana Margaret) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1979.